Fabrication of ZnO and ZnO:Sb Nanoparticles for Gas Sensor Applications. (7th September 2010) - Kashyout, A. B.; Soliman, H. M. A.; Shokry Hassan, H.; Abousehly, A. M.
Abstract : ZnO and Sb-doped ZnO nanoparticles were successfully prepared using sol-gel technique. Different concentrations of triethanolamine (TEA) were utilized as the preparation procedure to act as complexing agent that enhances the doping probability of the formed Sb-doped ZnO nanopowder. Thick films of the prepared nanopowders were fabricated with spinner coating. Morphological characteristics, phase structure, chemical composition, thermal stability, and optical properties of the prepared nanopowders were measured and analyzed. The average crystallite size of ZnO and ZnO:Sb powders ranged between 19–28 nm according to the XRD calculations and TEM observations. The gas sensitivity of the homemade devices based on Sb-doped ZnO nanoparticles towardsO 2 andCO 2 gases as a function of temperature was measured and compared with undoped ZnO films. The gas sensitivity of the films was greatly improved after doping with Sb and reached its maximum value of 86% forO 2 gas at 93:7 wt% of Zn:Sb.